New Media Art Utilization in Commercial Photography: Innovative and practical research in the direction of women’s psychological healing - Sheng, Yan (International Journal of Global Economics and Management, 2024)
The women’s economy has become a rapidly growing segment of the Chinese economy in recent years. The growth of the "she-economy" is a reflection of the development of feminist thinking. In recent years, the topics of "acoustic family, workplace relationship, family structure, mental health, male-female relationship" have been emerging, and modern women are pursuing a deeper exploration of their inner self, and by deconstructing their relationship with the society, they are gradually focusing on their own remodeling. With economic independence, women’s more emotional spiritual world needs to be filled with more media. Photography has become a major part of women’s consumption in recent years, and the commercialization of photography has become a unique way for women to express themselves. The huge market potential prompts the development of commercial photography needs more diversified integration, combining women’s psychological healing with commercial photography to form a unique artistic expression and marketing strategy. It is the focus of this paper to explore commercial photography and new media development in a more innovative way, focusing on women’s perspectives and serving the public with more practicality.